Educational Transformation in the Muhammadiyah Renewal Movement: Continuity of 21st Century Education - Luthfi, Atabik; Rosyada, Dede; Rahmawan, Fery; Mujib, Ahmad; Özalp, Hasan (Universitas Muhammadiyah Magelang, 2025)
This study aims to explore the transformation of education within the framework of the Muhammadiyah renewal movement and its relevance in addressing the challenges of 21st-century education. Despite advancements in educational technology, many students still face difficulties in utilizing digital tools effectively. As a modernist Islamic movement, Muhammadiyah has long contributed to the development of Indonesia’s education system through a progressive and responsive approach to contemporary issues. Guided by the principle of tajdid (renewal), Muhammadiyah continues to innovate in curriculum design, teaching methods, the integration of Islamic values, and the use of technology in learning. This qualitative case study was conducted at SMA Muhammadiyah 14 Central Jakarta, focusing on 36 tenth-grade students. The evaluation results indicated a significant improvement in students’ cognitive and digital skills. Approximately 82% of students demonstrated increased competence in using various digital learning applications such as Google Classroom and Canva. The findings highlight both challenges and opportunities in educational transformation and propose a comprehensive, collaborative, and sustainable strategy. This includes strengthening human resources, enhancing infrastructure, and developing relevant curricula aligned with Muhammadiyah’s renewal principles.